Magnesium implantation as a continuous hydrogen production generator for the treatment of myocardial infarction in rats - Bin Wang; Shuang Pan; Chaoqun Nie; Rentong Zou; Jiaren Liu; Xue Han; Li Dong; Jiawen Zhang; Xinrui Yang; Mengshu Yu; Bowei Fan; Xiaojian Hong; et al. (Scientific Reports, 2024)
Abstract Molecular hydrogen is an emerging broad-spectrum antioxidant molecule that can be used to treat myocardial infarction (MI). However, with hydrogen inhalation, the concentration that can be reached within target organs is low and the duration of action is short, which makes it difficult to achieve high dose targeted delivery of hydrogen to the heart, seriously limiting the therapeutic potential of hydrogen for MI. As a result of reactions with the internal environment of the body, subcutaneous implantation of magnesium slices leads to continuous endogenous hydrogen production, leading to a higher hydrogen concentration and a longer duration of action in target organs. In this study, we propose magnesium implant-based hydrogen therapy for MI. After subcutaneous implantation of magnesium slices in the dorsum of rats, we measured hydrogen production and efficiency, and evaluated the safety of this approach. Compared with hydrogen inhalation, it significantly improved cardiac function in rats with MI. Magnesium implantation also cleared free radicals that were released as a result of mitochondrial dysfunction, as well as suppressing cardiomyocyte apoptosis.